If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 1) + (x + 5) + x = 180 Reorder the terms: (1 + x) + (x + 5) + x = 180 Remove parenthesis around (1 + x) 1 + x + (x + 5) + x = 180 Reorder the terms: 1 + x + (5 + x) + x = 180 Remove parenthesis around (5 + x) 1 + x + 5 + x + x = 180 Reorder the terms: 1 + 5 + x + x + x = 180 Combine like terms: 1 + 5 = 6 6 + x + x + x = 180 Combine like terms: x + x = 2x 6 + 2x + x = 180 Combine like terms: 2x + x = 3x 6 + 3x = 180 Solving 6 + 3x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3x = 180 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = 180 + -6 3x = 180 + -6 Combine like terms: 180 + -6 = 174 3x = 174 Divide each side by '3'. x = 58 Simplifying x = 58
| 10-4x-6=-48x+6 | | 7(y-9)=-9y+33 | | 2y+4=y+6 | | 13+n=31 | | -6+3y=24 | | 2v+7=-7 | | 12+3x=3x-3 | | 13-Y/3=X/2 | | 2/5x+1/10 | | 3(27-4y)+y=-23 | | 2(x-3)-2(x+1)=4x | | 1/2-x+3/2=2x-8 | | 3(27-4y)=-23 | | 1+(4/(x+1))=(-4/(x^2+x)) | | ax+by=3c | | 2x^3+2x^2+7x=0 | | 2n+7=8n+15 | | -8n-9(n+5)=-8n-12(-5+2n) | | 2(60+k)=7k | | 12x+3x=3x-3 | | 2x^3(5x-1)=0 | | 3(x+1)-4=5 | | 9x-4(x-5)=30 | | (3+7i)+(-7-4i)= | | 0x=15 | | 2(2.8-0.2y)-y=5 | | -8(3x-4)=92 | | 0.8(x+50)+0.2x=65 | | 2(60+x)=3x | | 3f-5g-f-2g= | | 20/2.24=x | | 2x+12=5-15x |